(untitled) (International Journal of Nursing Education, 2020)
The period of adolescence is considered as a developmental period that not only inculcates subjectivity tothe life but also improves the critical thinking labelling environmental processes. Disease and sufferingsare considered to be part of almost all age groups thus deteriorating physical and psychological well-beingas a whole. Moreover, the course of hospitalization during the phase of disease can lead to stress, delayedcoping mechanisms. The major factors that lead to the former are change in health shifts of the hospital staff,painful procedures, lack of social and peer engagements, separation from parents and most importantly lossof self-esteem. The process of hospitalization can lead to disturbed body image in the paediatric client, lowself-esteem and confidence, delayed milestones and poor mental abilities in a long run. In order to combatthe overwhelming physical and psychological conditions there is a need to develop a Resilience Scale thatwould help to identify the coping levels in the child and hence can help the health care professional tonprovide efficient quality care. Towards systematic developmental process there is a need to formulate aconceptual model with the inter-related concepts or abstractions that would be assembled in a rational andexplanatory scheme. The Conceptual framework is needed to be utilized through an extensive literaturereview supporting linkage of selected, interrelated concepts on the basis of Rosswurum and Larrabee Modelthat recognized the translation of research into practice. Resilience scale can further be developed throughimplementation of the conceptual; model that can help the health care professionals to provide psychologicaldistractions and effective coping strategies before providing the physical treatments thus helping with aneasy resilience.